Modification of Gloves for Water Cushion As An Injury Prevention During Tumor Removal Procedure in Prone Position: Case Report - Lestari, Listya Puji; Aulawi, Khudazi; Subekti, Tri (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
Background: Surgery in the prone position has been associated with various complications such as facial edema, pressure ulcers, and eye problems. It is important to prevent complications during prone position with head support. Modification of water cushions made from gloves to protect the facial area is often done, but needs to be considered between the benefits and risks to patient safety.Case: A 29 year old woman with a tumor of the occipital region. The patient underwent tumor removal surgery in a prone position for +/- 9 hours. During the operation, the patient uses water cushions from the glove that are placed on the forehead and two sides of the eye. The cushion burst during positioning and in the middle of the operation a water cushion fell. After surgery, the patient complained of blurred vision and facial swelling for 2-3 days.Conclusion: The cushion modification of gloves has the benefit of protecting the bony prominences of the face. Apart from that, the risks of using this modification need to be taken into account, such as the risk of contamination, risk of injury if the placement is uncorrect, and injury also can arise if the cushions shifts or falls due to poor fixation. The modifications can be improved by replacing the gloves used, the water used, and the level of elasticity of the cushion. They can also use head supports that have been proven effective and improve intraoperative monitoring.